Triflates Promoted One-Pot Synthesis of Functionalized Unsymmetrical New Dihydro-1h-Indeno[1,2-B]Pyridines Through Hantzsch Reaction under Ultrasonic Irradiation - Turhan, Kadir; Ozturkcan, S. Arda; Turgut, Zuhal (CHEM SOC PAKISTAN, 2012)
Yb(OTf)(3) and Sc(OTf)(3) catalyzed efficient Hantzsch reaction via four-component coupling reactions of aldehydes, diketone, ethylacetoacetate and ammonium acetate at ambient temperature and medium was described as the preparation of pyridine derivatives. The process presented here is operationally simple, environmentally benign and has excellent yield. Furthermore, the catalyst can be recovered conveniently and reused efficiently. All the same, the condensation of aldehydes, ethyl acetoacetate and ammonium acetate result dihydroindenopyridines in 87-98% yields under ultrasound irradiation with catalyst at room temperature. Compared to conventional methods, the main advantages of the present procedure are milder conditions, shorter reaction time and higher yields.
Keywords: Indenopyridine; Multi-component Reactions; Ultrasound; Hantzsch Reaction; Triflate; CALCIUM-CHANNEL BLOCKER; ONE-STEP SYNTHESIS; 3-COMPONENT CONDENSATION; EFFICIENT SYNTHESIS; CARBONYL-COMPOUNDS; DERIVATIVES; DESIGN; HETEROCYCLES; PYRIDINE; AGENTS; Chemistry